Expanding the Therapeutic Landscape: Exploring the Antimicrobial and Bioactive Potential of Mangrove-Derived Endophytic Fungi - Rovik, Anwar; Mariana, Afifah; Hidayat, Galang Anahatta; Rahman, Farras Alifia (Universitas Muhammadiyah Surakarta, 2025)
The escalating rise of antibiotic resistance poses a significant challenge to discovering new, effective antibiotics. This crisis represents one of the most critical threats to global health, potentially leading to a future where even minor infections could become fatal. Endophytic fungi have recently emerged as a promising source of novel bioactive compounds. This review highlights the potential of endophytic fungi isolated from mangrove vegetation to produce new antimicrobial agents. Mangrove-derived endophytic fungi are found in healthy leaves, hypocotyls, roots, stems, and flowers. The symbiotic relationship between mangrove vegetation and these fungi promotes the synthesis of diverse bioactive compounds, including newly discovered molecules such as cytospyrone, cytospomarin, penicibrocazines, thiocladospolides, coumarin, isocoumarins, and dihydroradicinin. Beyond their antimicrobial potential, these fungi also produce compounds with antifungal, antioxidant, anticancer, anti-inflammatory, anti-filarial, antibiofilm, influenza antiviral, antimycobacterial, and biological control properties. The traditional approach to antibiotic development is complex, challenging, costly, time-consuming, and labor-intensive. To overcome these obstacles, research must integrate machine learning for big data analysis and molecular-based exploration, including genomics, proteomics, and transcriptomics.